ANALISIS PENERAPAN PSAK 24 TENTANG IMBALAN KERJA PADA PT. ANGKASA PURA I (PERSERO) BANDARA SAM RATULANGI MANADO - Nefry, Pajow A.; Pangemanan, Sifrid S.; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Employee benefits are rewards give by an entity to workers for services provided by workers or for termination of employment contracts. The purpose of this study was to find out how the application of PSAK 24 concerning Employee Benefits at PT. Angkasa Pura Manado's Sam Ratulangi Airport. This research was conducted with a qualitative descriptive method through case studies at PT. Angkasa Pura I (Persero) Manado's Sam Ratulangi Airport by collecting data through interviews and analysis of documents obtained from companies that support research. The results of the study show that PT. Angkasa Pura I (Persero) has provided all employee benefits according to PSAK 24, namely short-term employee benefits, post-employment benefits, other long-term employee benefits and severance pay. Companies must maintain the application of employee benefits that are in accordance with PSAK 24 and keep up with the latest developments in the regulations on employee benefits in Indonesia.